Implementasi Manajemen Kurikulum Bahasa Arab: Faktor Pendukung dan Penghambat - Fatimatuzzahroh (Sekolah Tinggi Ilmu Tarbiyah Ibnu Sina Malang, 2022)
The success of the curriculum is determined by how the management is carried out. This study aims to collect data and information regarding the implementation of the Arabic language curriculum at SD Ummu Aiman ​​Lawang and the supporting and inhibiting factors. Curriculum management at the institution is an attraction for research because the curriculum is made independently by a team of Arabic language teachers and is supported by a supervisor appointed by the principal as the curriculum curriculum and subject teacher at the school. This study uses a qualitative method. The data sources of this research are: observation, interview, and documentation. The results of this study indicate: the implementation of Arabic language curriculum management at Umm Aiman ​​Elementary School has fulfilled the 6 main elements of curriculum management, namely: people are supervisors, curriculum team as well as Arabic teachers, large costs (money) due to online learning and offline, question and answer methods, lectures, and mubasyaroh as well as blended learning models, curriculum administration materials (PROTA, PROMES, basic competencies, materials, syllabus, RPE, RPP, and KKM), and markets. implementer of curriculum, implementer of learning and evaluation. While the supporting factors come from the school, the supervisor's message and the curriculum curriculum team, the supervisor's ability and the curriculum curriculum and the responses of students and guardians of students. While the inhibiting factors are the diagnosis of needs, the weakness of the instructional objectives, and the evaluation is not in accordance with the instructional objectives.